Li Shutong zhi Liu Zhiping shu xin ji : mo ji zhen cang ben - Guan, Jiping, 1962- (Shanghai Shi : Zhonguo chu ban ji tuan : Dong fang chu ban zhong xin, 2014)
Summary in vernacular field only.
Keywords: Hongyi, -- da shi, -- 1880-1942 -- Correspondence; Liu, Zhiping -- Correspondence